EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI SELF-EFFICACY SISWA - Vira Anisa (Mat-Edukasia, 2020)
The purpose of this study is to describe the understanding of mathematical concepts taught with the Jigsaw type cooperative learning model better than conventional learning of class IX students of Merangin 43 State Junior High School in 2019/2020 school year. This research uses a quantitative approach with an experimental method. The sampling technique uses simple random sampling. Data collection techniques using test and non-test. The test is in the form of problem description and non-test in the form of self-efficacy questionnaire. The analysis technique uses t-test, t-test and two-way anova. The test results state that: understanding of mathematical concepts both overall and with high, moderate and low self-efficacy with the type of jigsaw cooperative learning model is better than conventional approaches, and there is an interaction between the jigsaw type and conventional learning model cooperative learning in terms of student learning independence .